2017
DOI: 10.3389/fpsyg.2017.01307
|View full text |Cite
|
Sign up to set email alerts
|

Associations between the Application of Signature Character Strengths, Health and Well-being of Health Professionals

Abstract: Previous research has shown a positive relation between character strengths, well-being and health. The aim of this analysis was to identify relations between the application of signature character strengths (ASCS) at work, and well-being and health, among medical students (Study 1) and resident physicians (Study 2). We expected positive direct links between the constructs and indirect effects through emotional exhaustion. To test these hypotheses, 387 medical students in their first year and 136 resident phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 56 publications
3
32
3
Order By: Relevance
“…However, the applicability of judgment in private life mediated the relation of judgment and SWB ('phasic' strength) and possessing fairness, honesty, or kindness was an indicator for a significant positive relation with SWB. Previous results already suggested that the overall 'good character' (Hausler et al 2017a) as well as the applicability at work (Hausler et al 2017b) was significantly more closely related to PWB than to SWB. Therefore, one could interpret the existing results as supportive for the hypothesis of PWB and signature character strengths having a stronger reciprocal relationship already due to their respective definitions, in contrast to emotions and satisfaction in different life domains.…”
Section: Discussionmentioning
confidence: 85%
“…However, the applicability of judgment in private life mediated the relation of judgment and SWB ('phasic' strength) and possessing fairness, honesty, or kindness was an indicator for a significant positive relation with SWB. Previous results already suggested that the overall 'good character' (Hausler et al 2017a) as well as the applicability at work (Hausler et al 2017b) was significantly more closely related to PWB than to SWB. Therefore, one could interpret the existing results as supportive for the hypothesis of PWB and signature character strengths having a stronger reciprocal relationship already due to their respective definitions, in contrast to emotions and satisfaction in different life domains.…”
Section: Discussionmentioning
confidence: 85%
“…Indeed, the link between ASCS-W and work engagement was empirically demonstrated, for example, by Harzer and Ruch (2013) and Lavy and Littman-Ovadia (2017). A positive relationship with well-being was established, for example, by Linley et al (2010), Forest et al (2012) and in samples of medical students and resident physicians by Hausler et al (2017b).…”
Section: Research Hypothesesmentioning
confidence: 95%
“…Indeed, Hausler et al (2017c) reported stronger correlations between character strengths of medical students and PWB than SWB, and Hausler et al (2017b) found a stronger relation between ASCS-W and PWB than SWB among medical students and resident physicians.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Hence, the "Applicability of Character Strengths Rating Scale" ACS-RS (Harzer and Ruch, 2013) was developed to measure the individually perceived influence of four conditions: two external ones: (I) normative demands and (II) appropriateness of strength-related behavior in given situations; two internal ones: (III) perceived presence of factors that may facilitate or hamper strength-related behavior and (IV) intrinsic motivation to show certain behavior Ruch, 2012, 2013). Recently conducted cross-sectional studies with samples of medical students and physicians emphasized the important role of one's applicable signature character strengths (applicability of signature character strengths in the context of study and work = ASCS-S/-W; and private life = ASCS-P) to foster mental health, well-being, burnout and work-engagement (Hausler et al, 2017a;Huber et al, 2019;Strecker et al, 2019). Furthermore, Höge et al (2019) could demonstrate with a sample of hospital physicians that the ASCS-W at the first measurement (T1) had an impact on the perception of the socio-moral climate of the medical department at the second measurement (T2) and reversed effects of the socio-moral climate at T1 on the ASCS at work at T2.…”
Section: Introductionmentioning
confidence: 99%